The validation of a functional, isolated bladder model from a large animal - Parsons, Brian A.; Drake, Marcus J.; Gammie, Andrew; Fry, Christopher H.; Vahabi, Bahareh (Frontiers in Pharmacology, 2012)
Characterising the integrative physiology of the bladder requires whole organ preparations. The purpose of this study was to validate an isolated large animal (pig) bladder preparation, through arterial and intravesical drug administration, intravesical pressure recording and filming of surface micromotions. Female pig bladders were obtained from the local abattoir and arterially perfused in vitro. Arterial and intravesical pressures were recorded at varying volumes. Bladder viability was assessed histologically and by monitoring inflow and outflow pH. Arterial drug administration employed boluses introduced into the perfusate. Intravesical administration involved slow instillation and a prolonged dwell-time. Surface micromotions were recorded by filming the separation of surface markers concurrently with intravesical pressure measurement. Adequate perfusion to all bladder layers was achieved for up to eight hours; there was no structural deterioration nor alteration in inflow and effluent perfusate pH. Arterial drug administration (carbachol and potassium chloride) showed consistent dose-dependent responses. Localised movements (micromotions) occurred over the bladder surface, with variable correlation with fluctuations of intravesical pressure. The isolated pig bladder is a valid approach to study integrative bladder physiology. It remains viable when perfused in vitro, responds to different routes of drug administration and provides a model to correlate movements of the bladder wall directly to variation of intravesical pressure.